Black phosphorus composites with engineered interfaces for high-rate high-capacity lithium storage - Jin, Hongchang; Xin, Sen; Chuang, Chenghao; Li, Wangda; Wang, Haiyun; Zhu, Jian; Xie, Huanyu; Zhang, Taiming; Wan, Yangyang; Qi, Zhikai; Yan, Wensheng; Lu, Ying-Rui; et al. (Science (American Association for the Advancement of Science), 2020)
A focus of battery research has been the development of a range of lithium, sodium, and potassium cathodes, but improving anode materials is also an important goal. Silicon has shown some promise for replacing graphite because of its exceptional capacity, but the dramatic volume change during lithiation-delithiation processes often leads to failure. Jin et al. developed a composite that is made of black phosphorous and graphite in its core and covered with swollen polyaniline. In contrast to previous efforts, bonding between the carbon and phosphorous allows for a high charging rate without sacrifices in capacity and cycling stability. Science , this issue p. 192 Black phosphorus composites with engineered interfaces deliver high capacity, high rate capability, and long cycle life. High-rate lithium (Li) ion batteries that can be charged in minutes and store enough energy for a 350-mile driving range are highly desired for all-electric vehicles. A high charging rate usually leads to sacrifices in capacity and cycling stability. We report use of black phosphorus (BP) as the active anode for high-rate, high-capacity Li storage. The formation of covalent bonds with graphitic carbon restrains edge reconstruction in layered BP particles to ensure open edges for fast Li + entry; the coating of the covalently bonded BP-graphite particles with electrolyte-swollen polyaniline yields a stable solid–electrolyte interphase and inhibits the continuous growth of poorly conducting Li fluorides and carbonates to ensure efficient Li + transport. The resultant composite anode demonstrates an excellent combination of capacity, rate, and cycling endurance.